Co-inoculation of antagonistic Bacillus velezensis FH-1 and Brevundimonas diminuta NYM3 promotes rice growth by regulating the structure and nitrification function of rhizosphere microbiome - Wang, Jingjing; Zhao, Siqi; Xu, Song; Zhao, Wei; Zhang, Xiaoxia; Lei, Yu; Zhai, Huanhuan; Huang, Zhiyong (Frontiers in Microbiology, 2023)
Microbial inoculation with plant growth-promoting microorganisms (PGPMs) is one of the most promising technologies to solve the current global challenges. Co-inoculants is more efficient and stable than mono-inoculants. However, the growth promoting mechanism of co-inoculants in complex soil system is still poorly understood. In this study, the effects on rice, soil and the microbiome of the mono-inoculant Bacillus velezensis FH-1 (F) and Brevundimonas diminuta NYM3 (N) and the co-inoculant FN obtained in previous works were compared. Correlation analysis and PLS-PM were used to explore the primary mechanism of different inoculants promoting rice growth. We hypothesized that inoculants promoted plant growth i) by themselves, ii) by improving soil nutrient availability or iii) by regulating the rhizosphere microbiome in complex soil system. We also assumed that different inoculants had different ways of promoting plant growth. The results showed that FN significantly promoted rice growth and nitrogen absorption and slightly increased soil total nitrogen and microbial network complexity compared with F, N and the control (CK). B. velezensis FH-1 and B. diminuta NYM3 interfered with each other's colonization in FN. FN increased the complexity of the microbial network compared to F and N. The bacterial community of FN was quite different from CK and N, while the fungal community was not significantly different from other treatments. The species and functions enriched or inhibited by FN are part of F. The correlation analysis and PLS-PM results showed that inoculants (F/N/FN) promoted the growth of rice mainly by regulating the rhizosphere microbiome rather than by themselves or by improving soil nutrient availability. Co-inoculant FN promotes rice growth specifically by enhancing microbial nitrification function through enriching related species compared with F or N. This may provide theoretical guidance for the construction and application of co-inoculants in the future.